Engineered Polyploid Yeast Strains Enable Efficient Xylose Utilization and Ethanol Production in Corn Hydrolysates - Liu, Lulu; Jin, Mingjie; Huang, Mingtao; Zhu, Yixuan; Yuan, Wenjie; Kang, Yingqian; Kong, Meilin; Ali, Sajid; Jia, Zefang; Xu, Zhaoxian; Xiao, Wei; Cao, Limin (Frontiers in Bioengineering and Biotechnology, 2021)
The reported haploid Saccharomyces cerevisiae strain F106 can utilize xylose for ethanol production. After a series of XR and/or XDH mutations were introduced into F106, the XR-K270R mutant was found to outperform others. The corresponding haploid, diploid, and triploid strains were then constructed and their fermentation performance was compared. Strains F106-KR and the diploid produced an ethanol yield of 0.45 and 0.48 g/g total sugars, respectively, in simulated corn hydrolysates within 36 h. Using non-detoxicated corncob hydrolysate as the substrate, the ethanol yield with the triploid was approximately sevenfold than that of the diploid at 40 °C. After a comprehensive evaluation of growth on corn stover hydrolysates pretreated with diluted acid or alkali and different substrate concentrations, ethanol yields of the triploid strain were consistently higher than those of the diploid using acid-pretreatment. These results demonstrate that the yeast chromosomal copy number is positively correlated with increased ethanol production under our experimental conditions.